Towards a political economy of monetary dependency: The case of the CFA franc in West Africa - Kai Koddenbrock; Ndongo Samba Sylla (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2019)
This paper focuses on the most neglected case of monetary dependency: the CFA franc. This currency arrangement was born in 1945, during the colonial era, but it still operates in the same ways more than 70 years later in fourteen countries in Africa, mostly former French colonies. Engaging with the seminal African scholarship by Joseph Pouemi on internal and external monetary repression and the emergent literature on "financial subordination," we introduce the notion of the "chain of monetary dependency," consisting of an external and an internal part. We argue that the CFA franc provides an extreme but paradigmatic example of this chain. The CFA franc is paradigmatic because of the very strong external repression of monetary and financial policy through US dollar and euro dependence. Internally, the CFA franc arrangement radicalizes the constraints imposed on all central bank policies and bank-firm relations in the Global South and makes it more difficult to pursue growth strategies geared towards the well-being of the broader population.
Keywords: 330; CFA franc; colonialism; dependency; monetary sovereignty; money; West Africa